Analisa Keruntuhan Bendungan Batujai dan Pengga dengan Aplikasi HEC-RAS 5.0.7 - Maulida, Diah Fitri; Juwono, Pitojo Tri; Asmaranto, Runi (Fakultas Teknik, Universitas Brawijaya, 2021)
ABSTRACT: Batujai and Pengga Dam are cascade dams with homogeneous types, are authorized in 1982 and 1994. These dams are located at the same mainstream that ends at Alas Strait. Batujai and Pengga Dam break may occur due to overtopping and piping. According to HEC-RAS 5.0.7 simulation suggested that the collapsed of each or both dams has the biggest impact when conditioned with design flood of QPMF are due to overtopping, when the peak of discharge are at 2036.151 m3/second and 3204.089 m3/second, which caused 34.127 km2 and 107.025 km2 area to be flooded, with maximum inundation of 19.656 meters and 19.837 meters. According to InaSAFE, if the collapse of these dams were merged, reported that there are 34 villages and 29,100 people are exposed to the risk, classified with high disaster risk. The cost that has to be paid by the damâ€™s owner due to the collapse is estimated to be Â Rp 201,584,808.36/Ha or Rp. 2,845,409,886,907 in total.